Regulation of Frizzled-Dependent Planar Polarity Signaling by a V-ATPase Subunit. - Hermle, T.; Saltukoglu, D.; Grünewald, J.; Walz, G.; Simons, M. (Current Biology, 2010)
Frizzled (Fz) is a seven-pass transmembrane receptor that acts in both Wingless (Wg) and planar cell polarity (PCP) pathways. A prerequisite for PCP signaling is the asymmetric subcellular distribution of Fz. However, the regulation of Fz asymmetry is currently not well understood. Here we describe that the transmembrane protein CG8444 (here termed VhaPRR) is needed for PCP signaling in Drosophila. VhaPRR is an accessory subunit of the vacuolar (V)-ATPase proton pump, but it also functions as a receptor for (pro)renin (PRR) in mammals. We show that VhaPRR function is tightly linked with Fz but not other PCP core proteins. Fz fails to localize asymmetrically in the absence of VhaPRR, and this is accompanied by prehair mispolarization of pupal wing cells. In addition, VhaPRR forms a protein complex with Fz receptors and interacts genetically with Fz in the Drosophila eye. VhaPRR also acts as a modulator of canonical Wnt signaling in larval and adult wing tissue. Its loss leads to an expansion of the Wg morphogen gradient and a reduction of Wg target gene expression. The requirement for additional V-ATPase subunits suggests that proton fluxes contribute to normal Fz receptor function and signaling.